THE SYMBOLISM OF COLORS IN COPTIC ART - Abouarab, Mohamed Ahmed Radí (2012)
The colors represent varied symbolism: cosmic symbolism, biological, physiological, psychological, or national-aesthetic. The colors and symbols have the same meanings in the culture of the various ancient peoples, coincidentally carries a universal common language that is closely related to religion. The coincidence of the symbols of the colors surprised scientists and researchers, which removed a key conclusion: the unity of religions in their human essence, the big test is the meaning and symbolism of the colors, which is the same for all peoples and all times. We analyze the use of color in Coptic art and how they transmit the Christian religious message.